Biobanks in the era of big data: objectives, challenges, perspectives, and innovations for predictive, preventive, and personalised medicine - Kinkorová, Judita; Topolčan, Ondřej (The EPMA journal, 2020)
Biobanking is entering the new era-era of big data. New technologies, techniques, and knowledge opened the potential of the whole domain of biobanking. Biobanks collect, analyse, store, and share the samples and associated data. Both samples and especially associated data are growing enormously, and new innovative approaches are required to handle samples and to utilize the potential of biobanking data. The data reached the quantity and quality of big data, and the scientists are facing the questions how to use them more efficiently, both retrospectively and prospectively with the aim to discover new preventive methods, optimize treatment, and follow up and to optimize healthcare processes. Biobanking in the era of big data contribute to the development of predictive, preventive, and personalised medicine, for every patient providing the right treatment at the right time. Biobanking in the era of big data contributes to the paradigm shift towards personalising of healthcare.
Keywords: Machine learning; Healthcare; Economy; Diabetes; Biomedical research; Cancer; Stroke; Population screening; Biobanks; Computation analysis; Personalised treatment algorithms; Information technologies; Patient benefits; Liquid biopsy; Innovations; Services; Implementation; Predictive preventive personalised medicine; Artificial intelligence; Big data